Effect of Drying Time on Morphology and Photovoltaic Characteristics of Polymer Solar Cells of Bis-PCBM/P3HT Composites. (11th August 2016) - Nagai, Masaru; Gao, Wenjuan; Huang, Wei; Yamamoto, Hideki; Yoshida, Yuji
Abstract : Slow drying has been proposed as a way to improve the performance of polymer solar cells (PSCs) where the drying time for the coated films is increased using a condensed solvent vapor atmosphere. This work investigated the slow drying mechanism by using PSCs consisting of poly(3-hexylthiophene-2, 5-diyl) (P3HT) and bis-[6, 6]-phenyl-C61-butyric acid methyl ester (bis-PCBM) and focusing on the phase-separated morphology of bulk heterojunction films. With conventional spin casting, the power conversion efficiency (PCE) of the cells was very low (0.83%). The application of slow drying resulted in notable improvements in the short-circuit current density (5.85 → 8.07 mA/cm 2 ) and fill factor (0.12 → 0.55). Optimization of the thermal annealing and cathode interfacial conditions resulted in a high PCE of 4.05%. As the drying time was increased, the P3HT domains changed from connected band-like shapes to small separated ball-like shapes. The mechanism for this effect of slow drying on the bis-PCBM/P3HT cell characteristics is understood as follows: The slow drying causes the P3HT domains to separate into small pieces, which causes the area of the p−n interfaces to increase, resulting in an increase in free carrier generation and increased the short-circuit current density of PSCs.